A digital image correlation analysis on a sheet AA6061-T6 bi-failure specimen to predict static failure. (August 2018) - Farahani, Behzad V.; Belinha, Jorge; Amaral, Rui; Tavares, Paulo J.; Moreira, Pedro
Abstract: The failure prediction on the mechanism of fracture in fine grained sheets is an unsolved problem in the framework of non-linear plastic damage and fracture mechanics. Several engineering ductile materials exhibit inelastic behaviour with corresponding large deformations. This work hence focuses on a bi-failure specimen made of an Aluminium alloy AA6061-T6 under a tensile loading circumstance with a geometry adapted to determine the failure phenomenon at high and low stress triaxiality states. A 3D non-contact full-field optical technique, Digital Image Correlation, DIC, is employed to process the experimental data in which the force/displacement response in addition to the internal fields are thereby documented. One of the purposes of the specimen's geometry is to test the robustness of proposed DIC procedure. So, to further pursue the failure phenomenon, an uncoupled model, Gurson–Tvergaard–Needleman (GTN), is computationally implemented using an explicit finite element analysis. Encouraging numerical results were achieved from Finite Element Method (FEM), validating the proposed model. Besides, the failure evolution analysed by the experimental data clearly elucidate failure modes. Considering all successful results, it can be concluded that the objectives of the present study were prosperously fulfilled revealing that the proposed procedure is feasible and efficient to predict the damage and failure phenomena on sheet AA6061 bi-failure specimens. Highlights: An AA6061-T6 bi-failure specimen is tested under a uniaxial tensile condition to study failure. Standard bi-failure specimen is geometrically modified to reach the study's goals. Experimental data is analyzed by means of DIC to obtain force/displacement and internal fields. The model is numerically simulated using FEM formula extended to GTN damage criterion. Obtained numerical results are close with DIC solution, validating the methodology proposed.